Difficulties encountered by hospitalized Syrian refugees and their expectations from nurses - Sevinc, S.; Kilic, S. P.; Ajghif, M.; Ozturk, H.; Karadag, E. (Wiley, 2016)
Background: Treating patients with care and respecting their cultural values are key factors necessary to enhance the quality of nursing care. Aim: The objective of this study was to explore and describe the difficulties experienced by hospitalized Syrian refugees and their expectations from nurses and hospital administration. Methods: We used a descriptive qualitative research approach to engage 30 Syrian refugees undergoing treatment in internal medicine who met the study criteria. Data were collected using a descriptive questionnaire and a semi-structured interview with open-ended interview questions. Interview transcripts were analysed using an inductive coding approach. Descriptive questions were analysed and presented via number and percentage. Other data were assessed using content analysis methods. Results: Three major themes were developed following the analysis of the interviews. We determined that the refugees who participated in the study experienced difficulties in communicating, meeting their personal needs and correctly following treatment instructions. They also had certain expectations from the hospital administration and nurses, and they felt gratitude for both nurses and the nation of Turkey. Conclusions: The results of this study, shared with the executive administration of the hospital, may result in new policies which will help new Syrian refugee patients and patients with similar needs to have better experience related to patient care, communications and meeting personal needs. Implication for nursing and health policy: It is important that nurses and other healthcare provider consider the difficulties and expectations of refugees regarding healthcare services and include same in the development of provider training programmes. Development of public health welfare and employment law and policies help to lay the groundwork for successful integration of refugees in new cultures and countries.
Keywords: Difficulties; Expectations; Syrian Refugees; Refugees; Nursing; Qualitative Research